Pharmacology of vitamin D - Glossmann, H. H. (Osteologie, 2011)
A main source of food for ancient humans (“hunter-gatherers”) was fresh meat. It contains much more 25(OH) vitamin D3 (25[OH]D3) than vitamin D3. It seems likely that in northern Europe, where vitamin D is in short supply during the extended winter season, evolutionary forces may have led to optimization of intestinal absorption of 25(OH)D3: excellent oral bioavailability (60 – 80 %) and little inter-individual variation. 25(OH)D3 could be considered the ideal oral “sunshine equivalent” for rapid and reliable restoration of an adequate vitamin D status e. g. in clinical situations. Unless biliary and pancreatic secretion or epithelial function in the small intestine is compromised, vitamin D3 in „pharmacological doses” is absorbed by 60 – 100 % as a „blind passenger” together with longchain fatty acids and cholesterol. The question is raised whether very low amounts of the vitamin (as in the diet) are absorbed by a more active (“second order”) mechanism. Experimental evidence obtained from cell culture systems indeed suggests that vitamin D3 can be taken up in part from enterocytes via the same complex, tightly regulated and saturable transport system as is e. g. cholesterol. The ezetimibe drug receptor NPC1L1 may play a role in this process. The Apolipoprotein Epsilon 4 genotype occurs in a north-south gradient in Europe. Allele frequencies are as high as 30 % in Finland and much lower, 5 %, around the Mediterranean Sea. The Epsilon 4 genotype may have been selected in the north because it enables more vitamin D to be obtained from food. The association of higher levels of 25(OH)D3 in humans with the Epsilon 4 genotype, together with evidence from knock-in mice, supports this hypothesis. It is possible, but as yet unproven, that this “lipid-thrifty” genotype is the cause of excess cardiovascular mortality sometimes observed in cohorts with high serum concentrations of 25(OH)D. Latitudinal gradients for mutations in the enzyme delta-7-dehydrocholesterol reductase (DHCR-7) suggest that similar evolutionary adaptations occurred for vitamin D synthesized in the skin following sun exposure.
Keywords: Vitamin D; Apolipoprotein E; intestinal transport; calcidiol plasma levels